Stemflow infiltration areas into forest soils around American beech (Fagus grandifolia Ehrh.) trees. Issue 2 (11th November 2021) - Llorens, Pilar; Latron, Jérôme; Carlyle‐Moses, Darryl E.; Näthe, Kerstin; Chang, Jeffrey L.; Nanko, Kazuki; Iida, Shin'ichi; Levia, Delphis F.
Abstract: The size of stemflow infiltration areas around the boles of trees is currently a topic of interest and debate within the hydrologic community. There is a gap in our knowledge of stemflow infiltration areas in many wooded ecosystems and a need for more than the few studies that have examined stemflow infiltration areas directly. Hence, this field study was specifically undertaken to mitigate the existing data gap by providing direct measurements of stemflow infiltration areas from high stemflow‐producing American beech ( Fagus grandifolia Ehrh.) trees. Different stemflow rates (290, 72 and 31 L h −1 ) were simulated using dye‐infused stemflow and the areas of stemflow infiltration around four trees determined by measuring the areal extent of dye on the soil surface. Our results revealed that stemflow infiltration areas ranged from 0.0035 to 0.0951 m 2  tree −1 . The mean basal area funnelling ratio was 46.5 ± 1.8, whereas the funnelling ratios per unit infiltration areas, F P, I t, were between 32.0 and 258.4. Despite intentionally high stemflow rates, chosen to compensate for the high infiltration capacities of forest soils, these results reinforce the fact that stemflow is an extremely localized input in natural forests. Thus, these results, even if specific to F. grandifolia within a particular forest and soil type, support a growing body of work indicating that stemflow infiltration areas are usually <1 m 2, and often much smaller, in natural forests. Moreover, the high values of F P, I t provide further evidence indicating that stemflow inputs are important for the development of hot spots in near‐trunk soils.